Islamic Political Characteristics (Study In Perspective Of Sunni Political Doctrine) - Bukhari Bukhari (Proceeding International Seminar of Islamic Studies, 2019)
This study discusses the political characteristics of Sunni Islam which are related to the doctrine of Sunni Politics. Many argue that the Islam that finally prevailed in this country is Sunni Islam. From this discussion are the political ideals adopted by Muslim kings in ancient times were Sunnis. The form and content of the ideals will be the task of this study to find out how Sunni political doctrine is towards the State and power. However, in this study it is argued that, whatever becomes the doctrine of Sunni politics towards the State and the power of ideals taken, the version of a Sunni political figure is likely to have developed around power. In other words, scholars and kings are two sides of the same coin. While the scholars need the support of the kings for the legitimacy of his authority. In the power of the head of state, the thought of this Sunni political figure formulated that there could be no opposition or opposition to the head of state. The Head of State is absolute in his power, taking the fight against the leader or the opposition. Therefore, the result of the thought of the Sunni figure is that the head of the State is the shadow of Allah on the face of the Earth.